PENINGKATAN KAPASITAS GURU SMA MUHAMMADIYAH 2 MELALUI RANCANGAN PEMBELAJARAN BASED ARTIFICAL INTELLIGENCE - Utami, Putri Yuli; Hakiki, Muhammad; Ruhama', Ufi (Universitas Mataram, 2024)
The advent of artificial intelligence (AI) has facilitated the creation of more interactive, personalised and effective learning media, including quizzes and video lessons tailored to students' needs. This is achieved through the use of sophisticated tools such as ChatGPT and Lumio. The objective of the training is to enhance the comprehension and proficiency of the teachers at SMA Muhammadiyah 2 Kota Pontianak in the creation of AI-based learning materials utilising Chat GPT and Lumio. The training was conducted in two phases: an introduction to ChatGPT and Lumio, and a training programme on the design of AI-based learning materials for teachers. The post-test evaluation demonstrated an average increase of 85% in knowledge, information and insight among the teachers in the use of ChatGPT and Lumio for the development of innovative, creative and interactive AI-based learning materials for students.